2016
DOI: 10.1111/jgs.14034
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Drug Burden in Persons with Dementia Taking a Cholinesterase Inhibitor: The Effect of Multiple Physicians

Abstract: ObjectivesTo explore the association between the number of physicians providing care and anticholinergic drug burden in older persons newly initiated on cholinesterase inhibitor therapy for the management of dementia.DesignPopulation‐based cross‐sectional study.SettingCommunity and long‐term care, Ontario, Canada.ParticipantsCommunity‐dwelling (n = 79,067, mean age 81.0, 60.8% female) and long‐term care residing (n = 12,113, mean age 84.3, 67.2% female) older adults (≥66) newly dispensed cholinesterase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
(49 reference statements)
3
20
1
2
Order By: Relevance
“…A number of risk factors for cognitive decline had been reported, such as depressed mood, comorbidities, polypharmacy, use of antipsychotics and frailty, and anticholinergic burden remained to be an independent risk for cognitive decline. In the present study, we found CV agents with anticholinergic properties were the most commonly used item among patients with or without using antipsychotics, which was different from other epidemiological studies . The CV agents listed in the ACB scale included atenolol, captopril, digoxin, dipyridamole, furosemide, hydralazine, isosorbide, metoprolol, nifedipine and so on, which could be easily overlooked by clinicians.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…A number of risk factors for cognitive decline had been reported, such as depressed mood, comorbidities, polypharmacy, use of antipsychotics and frailty, and anticholinergic burden remained to be an independent risk for cognitive decline. In the present study, we found CV agents with anticholinergic properties were the most commonly used item among patients with or without using antipsychotics, which was different from other epidemiological studies . The CV agents listed in the ACB scale included atenolol, captopril, digoxin, dipyridamole, furosemide, hydralazine, isosorbide, metoprolol, nifedipine and so on, which could be easily overlooked by clinicians.…”
Section: Discussioncontrasting
confidence: 82%
“…In addition to the aforementioned findings, the present study also explored the impact of anticholinergic activities of non‐antipsychotic medications on short‐term cognitive decline. Antipsychotic drugs, especially resperidone, quetiapine and olanzapine, were the most commonly prescribed drugs in long‐term care facilities . These antipsychotics were well known by their anticholinergic properties, and were believed to contribute the majority of the adverse cognitive effects in anticholinergics .…”
Section: Discussionmentioning
confidence: 99%
“…Selection of independent variables was guided by a literature search 8,9,1928 and the Andersen Behavioral Model for Health Services Utilization (ABM) 29 . The ABM proposes that use of health services, including medications, is influenced by a combination of: predisposing factors, influencing need for healthcare based on their demographics; enabling factors, the environmental factors that facilitate or inhibit access to healthcare; and medical need factors or aspects of the individual’s health perceived by the individual or a medical professional as necessary for seeking healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…4 People with dementia also have high likelihood of comorbidities and associated polypharmacy. 7,8 Previous international studies have shown that prevalence of PIP in people with dementia is between 15% and 64%. 7,8 Previous international studies have shown that prevalence of PIP in people with dementia is between 15% and 64%.…”
Section: Introductionmentioning
confidence: 99%